Facilitators and barriers to occupational health and safety in small and medium-sized enterprises: a descriptive exploratory study in Ontario, Canada. Issue 3 (2nd July 2016) - Nowrouzi, Behdin; Gohar, Basem; Nowrouzi-Kia, Behnam; Garbaczewska, Martyna; Chapovalov, Olena; Myette-Côté, Étienne; Carter, Lorraine
Abstract : Purpose . The purpose of this particular study was to test a newly created instrument in describing the facilitators and barriers to occupational health and safety in small and medium-sized enterprises (SMEs) in Ontario, Canada. Methods . A cross-sectional design was used to identify the occupational health and safety culture of SMEs in public and private sectors in Ontario. Results . A total of 153 questionnaires were completed. The majority of respondents were female (84%) with a mean age of 49.8 years (SD 10.6). Seventy-four percent were supervisors. Seventy percent of respondents were from the private sector while 30% derived from the public sector including healthcare, community services, and non-profit organizations. Further, conducting regular external safety inspections of the workplace was found to be statistically associated with a safe work environment 2.88 95% CI [1.57, 5.27]. Conclusions . Strategies and training opportunities that focus on how to adapt occupational health and safety legislation to the nature and diversity of SMEs are recommended. Furthermore, employers may use such information to improve safety in their SMEs, while researchers can hopefully use such evidence to develop interventions that are applicable to meeting the occupational health and safety needs of SMEs.